Measurement Of Service Quality Using Servqual And Importance Performance Analysis Methods (Case Study: Umaha) - Gusti Adriansyah; Ika Widya Ardhiyani; Dimas Setyawan; Asri Dwi Puspita (IQTISHADequity jurnal MANAJEMEN, 2023)
This study aims to determine the quality of research on student satisfaction services at the Faculty of Engineering, Economics and Law, Maarif Hasyim Latif University so that it is based on the results of the analysis of the Servqual model of five dimensions of service quality to create quality services and is expected to have an impact on student satisfaction. This study used a population of 1,719 students from the Faculty of Engineering, Economics, and Law with a sample consisting of 462 students using clustering sampling technique. The collected data were analyzed on a Servqual scale. Several dimensions of servqual which include responsiveness, empathy, assurance, tangible, reliability. According to the results obtained from the calculation of the SERVQUAL score, it was found that the expectations of the informants and all actual items had negative values, so that it could be interpreted that all items certainly did not meet student expectations. The quality of service at UMAHA has not been able to satisfy all students, from the results of the integration of the servqual method and the results of the Cartesian diagram measurement, the dominant attribute is in quadrant IV, which means that the performance of Umaha services is at a higher level, but the desire or expectation of students for this variable is low.